The forkhead protein Fkh2 is a component of the yeast cell cycle transcription factor SFF - Pic, Aline (Oxford University Press, 2000)
In the yeast Saccharomyces cerevisiae, the MADS-box protein Mcm1, which is highly related to mammalian SRF (serum response factor), forms a ternary complex with SFF (Swi five factor) to regulate the cell cycle expression of genes such as SWI5, CLB2 and ACE2. Here we show that the forkhead protein Fkh2 is a component of SFF and is essential for ternary complex formation on the SWI5 and ACE2 promoters. Fkh2 is essential for the correct cell cycle periodicity of SWI5 and CLB2 gene expression and is phosphorylated with a timing that is consistent with a role in this expression. Furthermore, investigation of the relationship between Fkh2 and a related forkhead protein Fkh1 demonstrates that these proteins act in overlapping pathways to regulate cell morphology and cell separation. This is the first example of a eukaryotic transcription factor complex containing both a MADS-box and a forkhead protein, and it has important implications for the regulation of mammalian gene expression.